The Effectiveness of SAVI Approach-based Teaching Materials Oriented to Mathematical Connection Ability - Muhammad Daut Siagian; Suwanto Suwanto; Rini Sulastri (Universitas Syiah Kuala, 2020)
This study aims to analyze the effectiveness of SAVI approach-based teaching materials developed for mathematical connection ability. This study was research and development. The subjects were 36 Grade 8 students and a mathematics teacher and the objects were the SAVI approach-based teaching materials oriented to the mathematical connection ability. The effectiveness of the teaching materials measured by four aspects: (1) the observation of the teacher's ability to manage the learning should at least be in the